Effects of resveratrol in an animal model of osteoporosis: a meta-analysis of preclinical evidence - Zhao, Jinlong; Zhou, Guanghui; Yang, Junzheng; Pan, Jianke; Sha, Bangxin; Luo, Minghui; Yang, Weiyi; Liu, Jun; Zeng, Lingfeng (Frontiers in Nutrition, 2023)
Background: Resveratrol is a natural polyphenol compound that is widely present in herbal medicines such as Reynoutria japonica Houtt., Veratrum nigrum L., and Catsiatora Linn and is used in traditional Chinese medicine to treat metabolic bone deseases. Animal experiments have shown that resveratrol may have a strong treatment effect against osteoporosis (OP). The purpose of this study was to explore the efficacy of resveratrol in treating OP animal models based on preclinical research data. Methods: This study was completed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We searched the PubMed, Embase, Cochrane Library, and China National Knowledge Infrastructure (CNKI) databases from inception to May 8, 2023, to identify animal experiments on the treatment of OP with resveratrol. The effect sizes of bone mineral density (BMD), parameters of micro-CT, serum calcium, phosphorus, alkaline phosphatase (ALP) and osteocalcin were expressed as the mean differences (MDs) and 95% confidence intervals (CIs). RevMan 5.4 software was used for data analysis. Results: This meta-analysis included a total of 15 animal experiments, including 438 OP rats. The meta-analysis results showed that compared with the control group, resveratrol (<10, 10-25, 40-50, ≥ 60 mg/kg/day) significantly increased femoral and lumbar bone mineral density (BMD) in OP rats (P<0.05). Resveratrol (<10 mg/kg/day) significantly increased the BMD of the total body (MD=0.01, 95% CI: 0.01 to 0.01, P<0.001). In terms of improving the parameters related to micro-CT, resveratrol (40-50 mg/kg/day) can increase trabecular thickness and trabecular number and reduce trabecular spacing (P<0.05). Compared with the control group, resveratrol can reduce the concentration of calcium and phosphorus in serum but has no significant effect on serum ALP and osteocalcin (P>0.05). The results of subgroup analysis showed that resveratrol increased the whole-body BMD of SD rats (P=0.002) but did not improve the whole-body BMD of 3-month-old rats (P=0.17). Conclusions: Resveratrol can increase BMD in OP rat models, and its mechanism of action may be related to improving bone microstructure and regulating calcium and phosphorus metabolism. The clinical efficacy of resveratrol in the treatment of OP deserves further research.